PENGARUH MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENENDANG BOLA SISWA KELAS II SDK WAIOTI - Isaci Selestiano Rodriquez, Estrado; Nande, Paskalis (Jurnal Biogenerasi, 2025)
This article aims to determine the effect of audiovisual media on the kicking skills of second-grade students at Waioti Elementary School. Audiovisual media is media that includes moving images or films and sound. This research was a quantitative research with an experimental method using the Pre-Experimental One Group Pretest-Posttest Design model. The sample in this study consisted of 32 students, with the sampling technique using probability sampling, and data collection techniques used were observation and tests. The results of this study indicated that the result of the initial ability (pretest) before using audiovisual media was 50.39% or average ability. The result of the final ability (posttest) after using audiovisual media was 83.48% average ability as well. The test results using the t-test showed that the t value 15.265 > ttable 2.039 at a significance level of 5%. Hence, Ha was accepted and Ho was rejected It could also be seen from the significance value (2-tailed) 0.001 < 0.05, therefore Ho was rejected and Ha was accepted. So it was concluded that there was an influence of audiovisual media on the ball kicking skills of grade II students at SDK Waioti.